The Good and Beautiful God : Falling in Love with the God Jesus Knows - Smith, James Bryan (London Hodder & Stoughton Ltd., 2010)
Book One of the Apprentice Series, a course in spiritual transformation.
Include Appendix and Notes.
Falling in Love with the God Jesus Knows.
Keywords: Spiritual life